Energy drinks: a narrative review of their physiological and pathological effects. Issue 5 (27th May 2021) - Piccioni, Andrea; Covino, Marcello; Zanza, Christian; Longhitano, Yaroslava; Tullo, Gianluca; Bonadia, Nicola; Rinninella, Emanuele; Ojetti, Veronica; Gasbarrini, Antonio; Franceschi, Francesco
Abstract: The consumption of energy drinks (Edks) has increased significantly in past years, with a growing market that is estimated to reach $61 billion by 2021 worldwide. Several studies demonstrated the physiological and pathological effects of these substances contained in Edks. The most common ingredient contained in Edks is caffeine, which is commonly mixed with taurine, and B‐group vitamins. Scientific evidence of potentially serious adverse health effects are known, but it would be better to acquire more information regarding these beverages. We systematically checked Medical literature on MEDLINE‐Pubmed from inception to January 2020 to find studies and reports on Edks and adverse events. Edks consumption is specially related to cardiovascular effects as malignant arrhythmias. We found a significant focus on arrhythmogenic risk in patients affected by long QT syndrome or other predisposing conditions for QT elongation. Other pathological effects are known as gastrointestinal, vascular and neurological disorders. Edks, as well as all caffeinated beverages, should be taken with caution or avoided in select populations, such as patients suffering from cardiovascular or neurological illnesses; their use can unmask a sleepy life‐threatening disease.